Channel microband electrodes: A complete working surface for potential step transients - Bidwell, M; Alden, J; Compton, R (1996)
The strongly implicit procedure is used to simulate the chronoamperometric transient resulting from a potential step at a channel microband electrode. A working surface is presented which permits the analysis of data recorded at any flow rate, including cases where axial diffusion effects are significant, and for cells of arbitrary geometry.